Keeping it Clean: Plan Your Cleaning - Mary N. Harrison; Amanda Griffin; Randall A. Cantrell (EDIS)
This 1-page fact sheet lists the things you should clean as you go, those tasks you should do immediately, and tasks to do less often. Written by Mary N. Harrison, Amanda Griffin, and Randall A. Cantrell, and published by the UF Department of Family, Youth and Community Sciences, May 2014.